2020
DOI: 10.1515/opag-2020-0024
|View full text |Cite
|
Sign up to set email alerts
|

Walnut leaf extract-based green synthesis of selenium nanoparticles via microwave irradiation and their characteristics assessment

Abstract: AbstractSelenium nanoparticles (Se NPs) have predominant characteristics compared to that in their bulk usage due to their high surface-to-volume ratio. The walnut (Juglans regia L.) leaf extract containing different bioactive compounds that act as reductant and stabilizing agents has been used for the green synthesis of the Se NPs. Influences of two synthetic variables, namely, the amount of selenium salt solution ranging from 15 to 25 mL and the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Figure 1 illustrates the UV analysis of OPWsynthesized Se-NPs, which reveals a significant peak at 295 nm. Due to the formation of the Se-NPs' surface-plasmon resonating (SPR) signal that may have been shown as a wide excitation wavelength (λ max) in the range of a wavelength of 270-400 nm, the creation of Se-NPs could be validated using the UV-Vis spectrophotometer [16,[37][38][39]. Se-NPs have a prominent peak in their UV-Vis spectrum of about 295 nm, which is indicated to spherical Se-NPs [16,37,38].…”
Section: Green Biosynthesis Of Se-nps Using Opwmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 illustrates the UV analysis of OPWsynthesized Se-NPs, which reveals a significant peak at 295 nm. Due to the formation of the Se-NPs' surface-plasmon resonating (SPR) signal that may have been shown as a wide excitation wavelength (λ max) in the range of a wavelength of 270-400 nm, the creation of Se-NPs could be validated using the UV-Vis spectrophotometer [16,[37][38][39]. Se-NPs have a prominent peak in their UV-Vis spectrum of about 295 nm, which is indicated to spherical Se-NPs [16,37,38].…”
Section: Green Biosynthesis Of Se-nps Using Opwmentioning
confidence: 99%
“…Due to the formation of the Se-NPs' surface-plasmon resonating (SPR) signal that may have been shown as a wide excitation wavelength (λ max) in the range of a wavelength of 270-400 nm, the creation of Se-NPs could be validated using the UV-Vis spectrophotometer [16,[37][38][39]. Se-NPs have a prominent peak in their UV-Vis spectrum of about 295 nm, which is indicated to spherical Se-NPs [16,37,38]. The resulting green synthesis of Se-NPs is easy, environmentally safe, and cost-effective, and the NPs produced are non-toxic and length of 270-400 nm, the creation of Se-NPs could be validated using the UV-Vis spectrophotometer [16,[37][38][39].…”
Section: Green Biosynthesis Of Se-nps Using Opwmentioning
confidence: 99%
See 1 more Smart Citation
“…Achieved narrow and sharp picks for the most fabricated Se NPs using synthetic methods indicated the high homogeneity and uniformity of the prepared Se NPs. Sheikhlou et al had already provided Se NPs using walnut leaf extract and microwave heating, with PDI of 0.206 [32].…”
Section: Effectiveness Of the Synthesis Methods On Characteristics Ofmentioning
confidence: 99%
“…Numerous researches revealed that high values of zeta potential (>+30 and <−30) for the mixture solution containing made inorganic NPs show their high stability [19,21]. Sheikhlou et al made Se NPs using the walnut leaf extract and microwave heating, with a zeta potential value of −24.7 mV [32]. 4].…”
Section: Effectiveness Of the Synthesis Methods On Characteristics Ofmentioning
confidence: 99%